S118 Can fractional exhaled nitric oxide help predict asthma in british foundry workers?. (15th November 2016) - Wiggans, RE; Robinson, E; Sumner, J; Codling, A; Lewis, L; Barber, CM
Abstract : Background: Foundry work may involve exposure to respiratory sensitisers and irritants. There is limited evidence for the use of FENO in occupational settings, and particularly in foundries. Aim: To examine the usefulness of FENO in identifying foundry workers at risk of asthma. Methods: Foundry workers undertook a respiratory questionnaire. Spirometry (Ndd Easy on-PC Spirometer, Zurich) and FENO (NOBreath, Bedfont Scientific, Kent) were measured to ATS/ERS standards. The ATS upper limit of normal (ULN) of 50 parts per billion (ppb), or 45.9ppb for current smokers, determined the high FENO category (FENO >ULN). Workers with FENO >ULN were compared with those with at least one work-related respiratory symptom (WRRS) and those with obstructive lung function (FEV1 /FVC <0.7) using Chi Square and Fisher's Exact Tests. Results: 351 workers (350 men, 99%) participated. 350 workers had a valid FENO performed. Arithmetic mean FENO was 30.2ppb (95% CI: 27.3–33.2); geometric mean (GM) FENO 20.8 (18.9–22.9) ppb. FENO exceeded the ULN in 61 (17%) workers. Average age for the FENO >ULN group was 41.5 (95% CI: 38.3–44.7), with a mean of 15.8 (12.4 – 19.2) years working in the foundry industry. Workers in the FENO >ULN group were significantly more likely to have a current diagnosis of asthma (12% vs 5%, p < 0.05), have ever suffered allergies (55% vs 31%, p < 0.01), or report work-related shortness of breath (3% vs 0%, p < 0.05). Fourteen workers (4%) had a FENO >ULN and WRRS (Figure1 ). Of these 14, only 2 (14%) had a current diagnosis of asthma (Fisher's p = 0.20). Eight (2%) workers had a FENO > ULN and FEV1 /FVC <0.7, though only 2 (25%) had a current asthma diagnosis (Fisher's p = 0.08). Conclusion: A significant proportion of foundry workers have FENO levels that exceed the ATS cut point for likely eosinophilic airway inflammation. Of these workers, most had a raised FENO but no WRRS or obstructive lung disease. Only a minority of workers with FENO >ULN and either WRRS or obstruction had a current diagnosis of asthma. FENO may be useful in identifying foundry workers at risk of asthma and warrants further study.